Marsha Is Magnetic - Ferry, Beth; Alvarez, Lorena (Boston, 2021)
Marsha tries scientific experiments to attract friends she can invite to her birthday party, but concludes that the best way to draw others is by being herself.
"A Junior Library Guild selection."
Keywords: Science -- Experiments; Juvenile fiction; Magnets -- Experiments; Juvenile fiction; Friendship -- Juvenile fiction; Families -- Juvenile fiction; Birthdays -- Juvenile fiction; Birthday parties -- Juvenile fiction; Science -- Experiments; Fiction; Magnets -- Experiments; Fiction; Friendship -- Fiction; Family life -- Fiction; Birthdays -- Fiction; Birthday parties -- Fiction